ANALISIS PROGRAM PEMBERDAYAAN MASYARAKAT (Studi Kasus Kelompok Nelayan Minapolitan Desa Tideng Pale Induk Kecamatan Sesayap Kabupaten Tana Tidung) - Nia Kurniasih Suryana; Syamsul Bahari (J-PEN Borneo : Jurnal Ilmu Pertanian, 2019)
ABSTRACT Community empowerment program is a process of empowering the community to have a better quality of life. To improve the welfare of fishermen, the potential they have must be managed and utilized optimally. There are not a few community empowerment programs that fail to reach their goals. This study aims to determine the empowerment program that is run in the Minapolitan fishing group in the village of Tideng Pale Induk, Sesayap Subdistrict and find out the satisfaction of the Minapolitan fishermen group on the empowerment program in the Village of Tideng Pale Induk, Sesayap District. Samples were taken by means of a census of 8 people, analysis of data used descriptive qualitative analysis and Likert scale with 3 categories namely very satisfied, quite satisfied and not satisfied. The results showed that the scope of the Minapolitan program carried out in the Minapolitan fishing group included the input of the empowerment program consisting of the socialization of the Minapolitan program, the determination of the Minapolitan program target group, the formation of fishermen groups. The process of empowerment program consists of the forms of programs implemented, recipient participation, cooperation, the role of facilitator, program monitoring and evaluation. The output of the empowerment program consists of physical benefits, non-physical benefits and income. The satisfaction level of the Minapolitan fishermen group on the empowerment program which consists of indicators of the quality of the empowerment program, quantity of empowerment programs, timing of the empowerment program and the impact of empowerment programs has an index value of 25 which is quite satisfied. Keywords: Community Empowerment, Minopolitan, Fisherman Group ABSTRAKProgram pemberdayaan masyarakat  merupakan  suatu proses memandirikan masyarakat agar memiliki kualitas hidup yang lebih baik. Untuk meningkatkan kesejahteraan nelayan maka potensi yang dimiliki harus dikelola dan dimanfaatkan secara optimal. Tidak sedikit program pemberdayaan masyarakat yang gagal  mencapai tujuannya. Penelitian ini bertujuan mengetahui  program pemberdayaan yang dijalankan pada kelompok nelayan minapolitan di Desa Tideng Pale Induk Kecamatan Sesayap dan mengetahui kepuasan kelompok nelayan minapolitan terhadap program pemberdayaan di Desa Tideng Pale Induk Kecamatan Sesayap.  Sampel diambil dengan cara sensus sebnanyak 8 orang, analisis data yang digunakan analisis deskriptif kualitatif dan skala likert dengan 3 kategori yaitu sangat puas, cukup puas dan tidak puas. Hasil penelitian menunjukan Lingkup program minapolitan yang dijalankan di kelompok nelayan minapolitan antara lain input program pemberdayaan terdiri dari sosialisasi program minapolitan, penetapan kelompok sasaran program minapolitan, Pembentukan kelompok nelayan. Proses program pemberdayaan terdiri dari bentuk program yang dilaksanakan, partisipasi penerima, kerjasama, peran fasilitator, monitoring dan evaluasi program. Output program pemberdayaan terdiri dari manfaat fisik, manfaat non fisik dan pendapatan. Tingkat kepuasan kelompok nelayan minapolitan terhadap program pemberdayaan yang terdiri dari indikator kualitas program pemberdayaan, kuantitas program pemberdayaan, waktu pelaksanaan program pemberdayaan dan dampak program pemberdayaan memiliki nilai indeks 25 yang termasuk pada kategori cukup puas. Kata Kunci : Pemberdayaan Masyarakat, Minopolitan, Kelompok Nelayan